Comparative performance and emission characteristics of peanut seed oil methyl ester (PSME) on a thermal isolated diesel engine - Ozturk, Ugur; Hazar, Hanbey; Yilmaz, Fikret (Pergamon-Elsevier Science Ltd, 2019)
In this research, cylinder liners of a diesel engine were coated with a 150 mu m thick Fe2B layer using boronizing method. The upper surface of the piston was coated with a 300 mu m thick CoNiCrAlYttra + NiCrBSi layer by using plasma spraying method. D-2, biodiesel (PSME-100) and blend (PSME-50) were used as test fuels. PSME fuel was produced through alkali catalyzed transesterification method. As-prepared fuels were used separately in coated (CE) and standard engines (SE) to compare performance and exhaust emission of both engines. In order to see the isolation effect of Fe2B layer, 3-D finite element transient-state analyses were carried out. According to the results, brake thermal efficiency (BTE) and exhaust gas temperature (EGT) of coated engine were considerably enhanced while brake specific fuel consumption (BSFC), CO, HC and smoke emission were decreased compared to those of standard engine. However, NOx emission of CE was higher than that of uncoated one, which was attributed to high combustion temperature and long combustion process in CE. These results were further confirmed with finite element simulation. The decreasing BSFC and increasing BTE for coated engine has been attributed to the elevated temperature of the combustion chamber by the effect of thermal insulation. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Boronizing; Isolation; Diesel engine; Biodiesel; Emission; Performance